EFFICIENT METHOD FOR DIRECT AND INDIRECT ORGANOGENESIS IN BIOFUEL CROP JATROPHA CURCAS - PURNA SHUKLA; VIJAY MAKWANA; DAKSHA BHATT; PUSHPA ROBIN (International Journal of Pharma and Bio Sciences, 2013)
Protocol for high frequency regenerants of J. curcas has been developed by the process of direct and indirect organogenesis from nodes and leaves as explants. Both the explants were initially inoculated on Murashige and Skoogs (MS) Basal medium. After a week they were transferred to MS medium supplemented with combinations of 6-benzylaminopurine (BAP) and Indole-3- butyric acid (IBA). MS medium supplemented with 3.0 and 5.0 μM IBA with 27.0 μM BAP supported quick callus initiation, while increasing the concentration of IBA to 7.5 μM led to delay in callusing. Emergence of shoot bud was first observed on medium supplemented with 27.0 μM BAP with 3.0 μM IBA. Of the combinations reported here 3.0 μM IBA with 4.5 μM and 27.0 μM BAP was found to be the best suitable medium for promoting multiple shoot regeneration with offshoot measuring 1.5-2.0 cm. Rooting was observed on MS basal medium.